Crystallization and diffraction analysis of the serpin IRS-2 from the hard tick Ixodes ricinus - Kovářová, Zuzana; Chmelař, Jindřich; Sanda, Miloslav; Brynda, Jiří; Mareš, Michael; Rezáčová, Pavlína (Acta crystallographica. Section F, Structural biology and crystallization communications, 2010)
IRS-2 from the hard tick Ixodes ricinus belongs to the serpin family of protease inhibitors. It is produced in the salivary glands of the tick and its anti-inflammatory activity suggests that it plays a role in parasite-host interaction. Recombinant IRS-2 prepared by heterologous expression in a bacterial system was crystallized using the hanging-drop vapour-diffusion method. The crystals belonged to the primitive tetragonal space group P4(3) and diffracted to 1.8 Å resolution. Mass-spectrometric and electrophoretic analyses revealed that IRS-2 was cleaved by contaminating proteases during crystallization. This processing of IRS-2 mimicked the specific cleavage of the serpin by its target protease and resulted in a more stable form (the so-called relaxed conformation), which produced well diffracting crystals. Activity profiling with specific substrates and inhibitors demonstrated traces of serine and cysteine proteases in the protein stock solution.
Keywords: Ixodes; Crystallization; Crystallography, X-Ray; krystalizace; Models, Molecular; Protein Structure, Tertiary; molekulární modely; krystalografie rentgenová; terciární struktura proteinů; klíště; Animals; serpiny; Serpins; zvířata